Exploring the interaction between the built food environment and intra-household gastronomy through photovoice in India - Ynion, Jhoanne; Banerjee, Deep; Custodio, Marie Claire; Samaddar, Arindam; Veetil, Prakashan Chellattan (TAFSSA, 2023)
Growing attention to food environment policies has been observed to address the multiple aspects of malnutrition (Kumar et al. 2023). In India, interventions promoting sustainable agriculture, small-scale farming, and equitable access to markets have been initiated to address the food and nutrition security of economically vulnerable groups. However, transformative interventions require deeper understanding specific contexts and a deep knowledge of the food environment. Moreover, simply improving food availability and access does not necessarily lead to better nor more equitable nutrition outcomes. Understanding the systemic cultural drivers of food choice, interventions promoting sustainable dietary choices can be more effectively contextualized leading to improved nutritional status. In this research note, we have adapted an expanded definition of the food environment using the socio-ecological framework (Downs et al., 2020) and the Gastronomic Systems Research (GSR) framework (Cuevas et al., 2017; Samaddar et al., 2020; Custodio et al., 2021). These frameworks allowed us to characterize the structures and processes in which individuals directly interact with the built food environment and the range of cultural factors influencing food choice for low to middle-income households. By employing Photovoice, a participatory and visual methodology that offers an emic approach by placing cameras in the hands of individuals facing socio economic disadvantage and/or marginalization (Pradeilles et al., 2021), we captured consumers’ experiences to identify the factors from the food environment that shape low-income households’ purchase of food, in general, and of healthier food options, in particular. Findings from this study could provide evidence for understanding consumption behaviors and associated factors, thereby providing insights into developing nutrition-sensitive interventions to improve the food environment that promotes healthy diets in low-income households.